(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of our study was to present our experience with the Rhomboid flap technique in the management of pilonidal sinus disease and to evaluate the morbidity and recurrence. Study Design: Cross-sectional, observational study. Place and Duration of Study: This study was conducted in the surgical department of Nishtar Hospital Multan Ward 4 surgical unit I, October 2011 to March 2012. Materials and Methods: Eleven patients were included, eight had previous surgical drainage of multiple natal cleft abscesses, and three had acute disease at the time of surgery. Nine patients had complex, recurrent pilonidal sinus. By using the Rhomboid transposition flap, we were able to excise the diseased area and close the defect. Operative time, hospital stay, healing time, wound infection, wound breakdown, return to normal activity and recurrence were assessed. Results: There were 10 males and one female with a median age of 23 years (range 17–32 years). Mean follow-up was 6 months (range 5-6 months). Mean operative time was 63.2 minutes (range 55-75 minutes). Hospital stay was 3.4 days (range 2-5). Postoperative morbidity involved superficial wound infection in two patients, superficial gangrene of wound edges in one patient and partial wound breakdown in one patient that settled with dressing in the out-patient clinic. All wounds healed and the median healing time was 15 days. There was no recurrence in our series. Median time to return to normal activity was 17.8 (range 10-27) days. Conclusion: Rhomboid flap is a useful technique in the treatment of advanced, difficult cases of pilonidal sinus disease. It has relatively low morbidity, allows early return to full activity and does not necessitate prolonged postoperative care. A larger series and longer follow up time is needed to assess the recurrence rate more adequately.